2002
DOI: 10.1111/j.1432-2277.2002.tb00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation and hepatitis C

Abstract: remain good indications for liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 89 publications
0
20
0
2
Order By: Relevance
“…1 Recurrent infection with HCV after OLT, however, is almost universal and is a significant cause of allograft dysfunction and allograft failure. [2][3][4] Preemptive interferon therapy (prophylaxis) in the early post-transplantation period may reduce the incidence and/or severity of recurrent HCV infection. In one study, 86 patients were randomized within 2 weeks after OLT to 3 million units of interferon alfa-2b or no treatment for 1 year.…”
mentioning
confidence: 99%
“…1 Recurrent infection with HCV after OLT, however, is almost universal and is a significant cause of allograft dysfunction and allograft failure. [2][3][4] Preemptive interferon therapy (prophylaxis) in the early post-transplantation period may reduce the incidence and/or severity of recurrent HCV infection. In one study, 86 patients were randomized within 2 weeks after OLT to 3 million units of interferon alfa-2b or no treatment for 1 year.…”
mentioning
confidence: 99%
“…9 Interestingly, many studies note that hepatitis C patients compared with controls have not shown a reduced graft or patient survival. [11][12][13] Recently, Forman et al, using the data from UNOS, reported that HCV-positive recipients were associated with an increased rate of death (hazard ratio, 1.23), especially in female recipients, compared with non-HCV recipients. 14 What factors may be influencing a more aggressive hepatitis course after transplantation?…”
Section: Natural History Of Hcv Posttransplantationmentioning
confidence: 99%
“…In 85% of cases, the virus establishes a chronic infection, culminating in chronic inflammation, cirrhosis, and, increasingly, hepatocellular carcinoma (HCC). Indeed, HCV is now the leading cause of HCC and is the most common reason for liver transplantation in the West (47). Treatment is presently limited to the use of type 1 interferon in combination with the nucleoside analogue ribavirin; this therapeutic regime is successful in 40 to 80% of patients, depending on virus genotype.…”
mentioning
confidence: 99%